The The Identification of Student Numerical Skill in Solving AKM (Minimum Assessment Competency) Question Type Assisted with Collaborative works platform at JHS - Nikmah Nurvicalesti; Ratnasari Ratnasari; Indri Kusuma Wardani (Jurnal Inovasi Matematika, 2025)
The study assessed the numeracy skills of junior high school students. The participants of this study were eighth-grade students from SMP Negeri 01 BP Peliung enrolled in ANBK. The tools in this study were a numeracy proficiency assessment and an interview questionnaire. The numeracy skill assessment in this study was administered to students utilizing Google Workspace and comprised six questions. The numeracy questions administered to students consist of AKM-type inquiries, including multiple-choice, complex-choice, true-false, and descriptive questions. This research involved interviews with six subjects, categorized into high, medium, and low numeracy skills, with two subjects in each category. This interview was conducted to assess students' numeracy skills based on seven components encompassed within three indicators of numeracy skills. Individuals with high numeracy proficiency demonstrate that all three indicators of numeracy are satisfied. Those with moderate numeracy proficiency meet only two indicators, specifically the skill to formulate situations and employ mathematical concepts, procedures, facts, and reasoning. Conversely, individuals with low numeracy proficiency fulfil only one indicator, the skill to formulate the situation.